1998
DOI: 10.1128/iai.66.5.2007-2017.1998
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Contact-Stimulated Formation of Filamentous Appendages by Salmonella typhimurium Does Not Depend on the Type III Secretion System Encoded by Salmonella Pathogenicity Island 1

Abstract: The formation of filamentous appendages on Salmonella typhimurium has been implicated in the triggering of bacterial entry into host cells (C. C. Ginocchio, S. B. Olmsted, C. L. Wells, and J. E. Galán, Cell 76:717–724, 1994). We have examined the roles of cell contact and Salmonellapathogenicity island 1 (SPI1) in appendage formation by comparing the surface morphologies of a panel of S. typhimurium strains adherent to tissue culture inserts, to cultured epithelial cell lines, and to murine intestine. Scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…Initial studies with tubular appendages of S. Typhimurium (60 nm in diameter) and epithelial MDCK cells or murine Peyer's patch follicle-associated epithelia (Ginocchio et al, 1994;Reed et al, 1998) described these as specific eukaryotic cell-induced structures (Ginocchio et al, 1994;Reed et al, 1998). In our experiments, tubular appendages of the same diameter connected bacteria to substrata or to bacteria in biofilms in the absence of eukaryotic cells.…”
Section: Describing Bacterial Appendages Connecting S Typhimurium Basupporting
confidence: 50%
See 1 more Smart Citation
“…Initial studies with tubular appendages of S. Typhimurium (60 nm in diameter) and epithelial MDCK cells or murine Peyer's patch follicle-associated epithelia (Ginocchio et al, 1994;Reed et al, 1998) described these as specific eukaryotic cell-induced structures (Ginocchio et al, 1994;Reed et al, 1998). In our experiments, tubular appendages of the same diameter connected bacteria to substrata or to bacteria in biofilms in the absence of eukaryotic cells.…”
Section: Describing Bacterial Appendages Connecting S Typhimurium Basupporting
confidence: 50%
“…R-type straight flagella of Salmonella are 5-11 nm (Mimori et al, 1995) and pili do not exceed 6-7 nm (Merz et al, 2000;Zhang et al, 2000), whereas aggregative fimbriae or curli are far smaller. High-resolution scanning electron microscopy studies revealed that contact with cultured epithelial cells results in the formation of unusually wide (60 nm in diameter) tubular appendages of S. Typhimurium attaching bacteria to the epithelial cells (Ginocchio et al, 1994;Reed et al, 1998). The formation of such appendages did not require de novo protein synthesis and was transient.…”
Section: Introductionmentioning
confidence: 99%
“…EspA is a component of a filamentous surface appendage that forms a contact between the bacterium and the eukaryotic cell surface (Knutton et al ., 1998). These structures resemble specific appendages (invasomes) that can be detected on the surface of S. typhimurium during epithelial cell invasion, although their relationship to the SPI‐1 type III secretion system is uncertain (Ginocchio et al ., 1994; Reed et al ., 1998). The SPI‐1 secretion system forms a needle‐like structure that spans the bacterial cell envelope (Kubori et al ., 1998).…”
Section: Discussionmentioning
confidence: 99%
“…These membrane sheaths were often beaded to a variable degree and often did not contain flagella filaments [114]. Outer membrane tubular appendages interconnect bacteria Salmonella typhimurium in biofilms and attach bacteria to eukaryotic cells and substrates [18,115,116]. The diameter of the appendages (60 nm) significantly exceeded the diameter of the bacterial flagella (15-20 nm) or pili (6-7 nm).…”
Section: Cytonemes In Cell Adhesion and Communication Of Parasitic Prmentioning
confidence: 99%